2014
DOI: 10.1175/jcli-d-13-00541.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal-Scale Variation of South Asian Summer Monsoon Onset and Its Relationship with the Pacific Decadal Oscillation

Abstract: The variation of the summer monsoon onset over South Asia was investigated by using long-term data of the onset over Kerala, India, during the 64-yr period from 1948 to 2011. It was found that the onset over Kerala shows variation on a multidecadal scale. In early-onset years, the sea surface temperature (SST) anomaly over the northern Pacific Ocean was very similar to the negative Pacific decadal oscillation (PDO). The stationary wave train related to the negative PDO reaches into central Asia and generates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 27 publications
5
32
0
Order By: Relevance
“…We also display the 30-yr running average of the PDO index to highlight its interdecadal component. We found the same increase in the correlation as reported by Watanabe and Yamazaki (2014) during the early 1970s, with values reaching statistical significance by 1975. This increase is concurrent with the strong upward trend of the 30-yr filtered PDO.…”
Section: B Long-term Relation Of Mok With Enso and Pacific Decadal Osupporting
confidence: 89%
See 1 more Smart Citation
“…We also display the 30-yr running average of the PDO index to highlight its interdecadal component. We found the same increase in the correlation as reported by Watanabe and Yamazaki (2014) during the early 1970s, with values reaching statistical significance by 1975. This increase is concurrent with the strong upward trend of the 30-yr filtered PDO.…”
Section: B Long-term Relation Of Mok With Enso and Pacific Decadal Osupporting
confidence: 89%
“…5) The recently described relationship between the PDO and MOK limited to the phases characterized by the shift from negative to positive PDO phases has been confirmed for two complete PDO cycles. Watanabe and Yamazaki (2014) postulated that a stationary wave train plays an active role in connecting both the North Pacific Ocean and South Asian monsoon region. Because of the limitation of their study to the period 1948-2011, they suggested that this link should be further addressed by using longer-term data.…”
Section: Summary and Remarksmentioning
confidence: 99%
“…The dynamics linking the ASM onset and interdecadal variability of the Pacific have been well addressed in previous works [ Kajikawa and Wang , ; Kajikawa et al ., ; Xiang and Wang , ; Watanabe and Yamazaki , ]. The direct driver of the earlier onset of the ASM is the earlier overturning of the meridional heat contrast between the Asian continent and the Indian Ocean in the premonsoon season.…”
Section: Mechanisms For the Wetting Trend Over The Tpmentioning
confidence: 99%
“…Xiang and Wang [] document the decadal shift in the Pacific basin to a “grand” La Niña‐like pattern in the 1990s in driving the earlier onset of the ASM since the late 1970s through the westward emanation of Rossby waves, based on numerical experiments. Watanabe and Yamazaki [] demonstrate that the negative Pacific Decadal Oscillation phase in recent decades is important for the earlier overturning of the meridional heat contrast in the ASM region via exciting a stationary wave train from the northern Pacific Ocean to central Asia.…”
Section: Mechanisms For the Wetting Trend Over The Tpmentioning
confidence: 99%
“…Krishnamurthy and Krishnamurthy (2013) showed that the warm (cold) phase of the PDO is associated with a deficit (excess) of rainfall over India in June-September. Recently, Watanabe and Yamazaki (2014) further found that the early onset of summer monsoon in Kerala, considered as the beginning of India's rainy season by many studies (e.g. Wang et al, 2009a), is closely associated with the negative PDO through the teleconnection of the stationary wave train, thus intensifying the land-sea thermal contrast.…”
Section: Onset Of the Asian Summer Monsoonmentioning
confidence: 98%